Gendered bordering practices in Swedish and Russian foreign and security policy. (May 2019) - Agius, Christine; Edenborg, Emil
Abstract: In recent years, border tensions have characterised Swedish-Russian security relations in the form of simulated strikes and military exercises in the Baltic Sea region. In this article, we show that while security tensions 'at the border' may be present, a complex process of gendered bordering underwrites Swedish and Russian foreign and security policy, seemingly pitching a progressivist and feminist Swedish foreign and security profile against Russian security performances that exhibit overt masculinist power. The tensions between Russia and Sweden appear imbued with gendered power relations. To analyse these forms of gendered bordering, we engage with Critical Border Studies by understanding bordering as practice, rather than theorising borders as 'static dividing lines' and by drawing on feminist security studies by examining bordering practices as constructions of masculinism, sexuality, and as a performance of gendered states. We argue that the gendered dynamics that inform state bordering practices are layered, complex, and contradictory. Rather than two opposing but consistent positions, we identify tensions and ambiguities within these subjectivities and examine how gendered bordering practices shape and militarise the state.